2020
DOI: 10.1007/s00604-020-04258-y
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxybutyrate dehydrogenase decorated MXene nanosheets for the amperometric determination of β-hydroxybutyrate

Abstract: MXene nanosheets of type Ti3C2Tx were modified with β-hydroxybutyrate dehydrogenase and then used as a biosensor for amperometric sensing of β-hydroxybutyrate. The MXene and the nanocomposite were characterized by X-ray photoelectron spectroscopy, field-emission scanning electron microscopy, X-ray diffraction, and Fourier-transform infrared spectroscopy. The MXene has a layered structure and proved to be an excellent immobilization matrix that provides good compatibility with the enzyme β-hydroxybutyrate dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…For example, Koyappayil et al reported that Ti 3 C 2 Tx nanosheets decorated with β-hydroxybutyrate dehydrogenase as a transducer platform for developing an electrochemical β-hydroxybutyrate biosensor with amperometric β-hydroxybutyric acid detection. The biosensor displayed a sensitivity of 0.480 µA/(Mm•cm 2 ), a wide linear range from 0.36 to 17.9 mM, and a LOD of 45 µM [168]. Another breakthrough in developing peptide-based electrochemical biosensors was reported by Xu et al, who designed a universal strategy for constructing ratiometric antifouling electrochemical biosensors based on multifunctional peptides 2D MXene nanomaterials loaded with AuNPs and methylene blue (MB) to PSA detection.…”
Section: Examples Of Nanobioengineered Platforms For Electrochemical ...mentioning
confidence: 99%
“…For example, Koyappayil et al reported that Ti 3 C 2 Tx nanosheets decorated with β-hydroxybutyrate dehydrogenase as a transducer platform for developing an electrochemical β-hydroxybutyrate biosensor with amperometric β-hydroxybutyric acid detection. The biosensor displayed a sensitivity of 0.480 µA/(Mm•cm 2 ), a wide linear range from 0.36 to 17.9 mM, and a LOD of 45 µM [168]. Another breakthrough in developing peptide-based electrochemical biosensors was reported by Xu et al, who designed a universal strategy for constructing ratiometric antifouling electrochemical biosensors based on multifunctional peptides 2D MXene nanomaterials loaded with AuNPs and methylene blue (MB) to PSA detection.…”
Section: Examples Of Nanobioengineered Platforms For Electrochemical ...mentioning
confidence: 99%
“…Operating at −0.35 V vs. Ag/AgCl, the developed biosensor displayed a linear range between 0.36 and 17.9 mM as well as a LOD of 45 µM. The sensor was tested for the determination of β-hydroxybutyrate analyte in (spiked) real serum samples [ 46 ]. Moreover, a mediator-free amperometric biosensor was designed for the detection of phenol.…”
Section: 2d Nanostructures: Synthesis Properties and Integration In Biosensing Designmentioning
confidence: 99%
“…The developed biosensor best operated at a potential of −0.35 V (vs. Ag/AgCl), displayed a linear range between (0.36 to 17.9 mM), a sensitivity of 0.480 μA mM −1 cm −2 , and a LOD of 45 μM. Later, the biosensor was successfully applied to the determination of β-hydroxybutyrate in (spiked) real serum samples [ 68 ].…”
Section: Classes Of Bioanalytical Sensors Based On Mxenesmentioning
confidence: 99%